Autoavaliação institucional: dimensões políticas e gestão democrática - Montemór, Maria Lúcia (Universidade Federal de São Carlos, 2013)
The movements and regulatory reforms, especially in the 1990, brought significant changes to the organization and management consequences as the public school, which arise from conceptions or practices of evaluating a given context. Knowledge of assessment methodologies of the school, or the Institutional Self Assessment, can stimulate the management team to work more collectively, participation valuing each and portraying the school as it is, from the point of view of their community. The Municipal School Professor Ali Homsi Salles Cunha in Sao Jose do Rio Preto − SP, created, recreated and effected in the period 1999-2010, a model of institutional selfevaluation itself through questionnaires processed in evaluation reports. In this dissertation, we used the cutout from 2006 to 2009 due to the significant changes that have occurred in this period and that have led to specific changes in the organizational culture of the school. We attempted to place a framework of theoretical and conceptual reference concerning the evaluation and Institutional Self-Evaluation in education and school; define the methodological procedures as presented searched the school and report the construction process of self-evaluation, showing it through analysis of documents, reports and other evaluative Institutional (Political Pedagogical Project, School Plan etc.). To this end, we prepared two broad categories of analysis: social and educational policies and organizational culture and management dimensions. From these categories, we created others with timely information for this investigation. Analyzed as before and after school was to establish annually the Evaluative Report and found that the changes in its organizational culture to have a democratic management. The methodology used was to work with questionnaire responses from parents/family segment and the evaluative reports collectively built the cutout of four years (2006- 2009). It was concluded that the self-assessments, developed, implemented and analyzed collectively by the institution, become facilitators tools to streamline diagnostics and troubleshooting, taking into account participation in the establishment of a democratic management process.
Keywords: Avaliação institucional; Cultura organizacional; Gestão democrática; Educação básica; Políticas públicas; CIENCIAS HUMANAS::EDUCACAO